PENGEMBANGAN SISTEM E-COMMERCE SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN KEWIRAUSAHAAN DI SMK N 2 PADANG - Geovanne Farell; Muhammad Giatman; Mukhlidi Muskhir; Hansi Effendi (Jurnal Teknologi Informasi dan Pendidikan, 2021)
This research was conducted at SMK N 2 Padang which aims to implement the e-commerce system as a learning medium for entrepreneurship education in order to increase the potential of students in entrepreneurship according to the chosen field of expertise. As well as preparing students to compete in the world of work and be able to open their own jobs by utilizing technology in the form of internet networks. The method used in this study is a Research & Development (Development Method) with a waterfall development model. This model consists of several stages including the planning stage, the software needs analysis stage, the software design stage, the implementation stage, and the maintenance stage. With the existence of an e-commerce system as a medium of learning in entrepreneurship education, students can understand business processes that utilize the internet network, be it the production process, the marketing process, or the transaction.